Peran Jalur Prestasi Non-Akademik (Olahraga) dalam SPMB Terhadap Pengembangan Bakat Olahraga Siswa di SMA Negeri Terawas - Taufik Pebri; Ahmad Gawdy Prananosa; Rusni Eka Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the role of the non-academic achievement pathway (sports) in the Student Admission Selection (SPMB) toward the development of students’ sports talents at SMA Negeri Terawas. The method used is a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation studies involving informants such as the vice principal for student affairs, SPMB committee members, sports coaches, and students admitted through the achievement pathway. The results show that the sports achievement pathway serves as an entry point for talented students to receive more structured coaching through extracurricular activities. The presence of these students also contributes positively to improving school achievements and identity in sports. In conclusion, the sports achievement pathway plays an important role in developing students' talents; however, its implementation still requires better support in terms of facilities, specialized coaches, and effective training time management. Keywords: Achievement Pathway, Sports, Talent Development, Senior High Scool, SPMB